Growth and Unemployment - Aghion, P.; Howitt, P. (Review of Economic Studies, 1994)
This paper analyses the effects of growth on long-run unemployment using a search model of equilibrium unemployment where growth arises explicitly from the introduction of new technologies that require labour reallocation for their implementation. The analysis uncovers and compares between two competing effects of growth on unemployment. The first is a capitalisation effect, whereby an increase in growth raises the capitalised returns from creating jobs and consequently reduces the equilibrium rate of unemployment. The second is a creative destruction effect whereby an increase in growth reduces the duration of a job match, thereby raising the equilibrium level of unemployment both directly, by raising the job separation rate, and indirectly, by discouraging the creation of job vacancies.